Writing the book of the world - Sider, Theodore (Oxford : Oxford University Press, 2011)
Theodore Sider presents a vision of metaphysics centred on the idea of structure. To describe the world we must use concepts that 'carve at the joints', so that conceptual structure matches reality's structure. This approach illuminates a wide range of topics, such as time, modality, ontology, and the status of metaphysics itself.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Metaphysics